2009
DOI: 10.1016/j.jaci.2008.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Local release of B cell–activating factor of the TNF family after segmental allergen challenge of allergic subjects

Abstract: Background Local production of IgA and IgE in the airways has been proposed to be an important event in both immune protection from pathogens and the pathogenesis of airway allergic diseases. Objective The objective of this study was to investigate the production of B cell-activating factor of the TNF family (BAFF), an important regulator of B cell survival and immunoglobulin class switch recombination, in bronchoalveolar lavage (BAL) fluid after segmental allergen challenge (SAC) of allergic subjects. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 40 publications
3
38
0
Order By: Relevance
“…The production of IL-1RA could be related to reports that Th9 cells suppress Th17-mediated inflammation (38,39). Th9 cells could be the source of BAFF released following allergen challenge of patients (40). The expression of CD103 by Th9 cells is consistent with a role for these cells at mucosal surfaces.…”
Section: Batf Expression In T Cells Is Required For the Development Osupporting
confidence: 58%
“…The production of IL-1RA could be related to reports that Th9 cells suppress Th17-mediated inflammation (38,39). Th9 cells could be the source of BAFF released following allergen challenge of patients (40). The expression of CD103 by Th9 cells is consistent with a role for these cells at mucosal surfaces.…”
Section: Batf Expression In T Cells Is Required For the Development Osupporting
confidence: 58%
“…In patients with asthma, serum BAFF level was found to be high in both IgE-mediated and non-IgE-mediated asthma suggesting that BAFF might reflect an inflammation in airways without any correlation to IgE antibodies production [12]. This concept was verified by, Kato et al, who demonstrated that following allergen exposure BAFF was upregulated locally in the airways of allergic subjects (asthma and allergic rhinitis) [13]. In atopic dermatitis, an increased serum BAFF level has been reported in children, but not in adults [14,15].…”
Section: Discussionmentioning
confidence: 89%
“…BAFF levels were also reported to be higher in the serum and bronchoalveolar lavage fluid of asthmatic patients when compared to normal individuals. These increased levels correlated with total number of lymphocytes, neutrophils and eosinophils (69). Based on these results it would seem that antigen induced production of BAFF may contribute to class switch recombination and immunoglobulin synthesis in B-cells.…”
Section: Acute/early Phase Responsementioning
confidence: 99%